2002
DOI: 10.1021/ol017147v
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Synthesis of 3,5-Disubstituted-2-pyridylpyrroles from the Condensation of 1,3-Diones and 2-(Aminomethyl)pyridine

Abstract: 3,5-Disubstituted- and 3,4,5-trisubstituted-2-(2-pyridyl)pyrroles may be synthesized efficiently from the novel condensation of 2-(aminomethyl)pyridine and 1,3-diones. The cyclization reaction was found to proceed through the intermediacy of a (2-pyridyl)methylimine. A marked dependence of the regioselectivity in the reaction of unsymmetrical diones on the presence of additional aminomethylpyridine suggests that two pathways to the product pyrroles are available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
70
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 17 publications
1
70
0
Order By: Relevance
“…There are just a few examples of the synthesis of pyridylpyrroles, including the photolysis of pyridylchlorodiazirines in the presence of 1-azabuta-1,3-dienes, [14] heterocyclization of acetylene with oximes of acetylpyridines [15][16][17][18] and dimethyl glyoxime [19] (the Trofimov reaction) [20] and the Paal-Knorr high-temperature condensation (170-190°C) of 1,3-diketones with 2-(aminomethyl)pyridine. [21] Of these methods, none is an obvious candidate to be simply modified for the synthesis of dipyrrolylpyridines. Although the ketoxime-acetylene route may look most appropriate for that, the specificity of oximes of diacetylpyridines, including their enhanced chelating power and that of the intermediates, [22] could seriously interfere with the synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…There are just a few examples of the synthesis of pyridylpyrroles, including the photolysis of pyridylchlorodiazirines in the presence of 1-azabuta-1,3-dienes, [14] heterocyclization of acetylene with oximes of acetylpyridines [15][16][17][18] and dimethyl glyoxime [19] (the Trofimov reaction) [20] and the Paal-Knorr high-temperature condensation (170-190°C) of 1,3-diketones with 2-(aminomethyl)pyridine. [21] Of these methods, none is an obvious candidate to be simply modified for the synthesis of dipyrrolylpyridines. Although the ketoxime-acetylene route may look most appropriate for that, the specificity of oximes of diacetylpyridines, including their enhanced chelating power and that of the intermediates, [22] could seriously interfere with the synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Although there are only a few metal complexes of pyridylpyrrolide in literature, it has been shown that this ligand can stabilize high-valent, polyhydride iridium complexes. [15][16][17][18][19][20][21][22][23] The pyridylpyrrolide derivative that will be implemented in this work is the ligand 3,5-bis(trifluoromethyl)-2-(2′-pyridyl)pyrrole [(X)(L)] (X = H + or K + ).…”
mentioning
confidence: 99%
“…In addition, selectivity for anti-Markovnikov over Markovnikov products (ca. Deprotonation of dmpp-H (3) [10] with KH in THF yielded green dmpp-K (4). However, significantly higher selectivities and turnover numbers (TONs) are needed to make these processes economical, so a broadly tunable system that can be modified both sterically and electronically is likely needed.…”
mentioning
confidence: 99%